Transferência de aprendizagem: um estudo com alunos e ex-alunos de programas de MBA - Silva, Patrícia Teixeira Maggi da (2014)
This research investigated the phenomenon of transfer of learning from the following guiding question: How is the process of transfer of learning obtained in MBA programs to the workplace, in the view of students and alumni? The overall objective was to understand the process of transfer of learning acquired in MBA programs to the workplace. The theoretical framework is grounded in the international literature and presents and analyzes the models that evaluated the transfer of learning in different types of educational activities, including the MBA itself. We also sought to understand the characteristics of the MBA as a program in management education. In this sense, it was presented a brief history of this program, contextualizing the model of MBA in Brazil and the main criticism it has received over the past few years. The research of descriptive character, was developed based on the assumptions of the basic or generic qualitative studies. This option was considered the most appropriate because it seeks to understand a phenomenon, from the perspective of the research participants, in this case, the MBA students. The interview was the main strategy used for data collection. Thirteen students and alumni of MBA with specialization from a higher education institution in the city of São Paulo were interviewed. The interviews were analyzed, allowing the generation of analytical codes hierarchically organized into categories, facilitating the analysis and interpretation of meanings. The main results reported in the research show that the student is the protagonist in the transfer of learning process from the MBA to the workplace. The factors related to the design of the course and the work environment were less significant. The results also revealed that the transfer of learning occurs in various disciplines throughout the course. Finally, it was found that the hard skills are easier to be transferred and generate faster results.